Ogroženost zaposlenih na področju nasilja v družini - Rosič, Jasmina (Socialno delo, 2016)
The fining so fare have indicated that user violence is common, especially in family services. Users in the field of domestic violence commonly do not willingly seek for services, resulting in violent behavior towards pracitioners. Several models for working with involuntary users, and guidelines for workin with users' violence were developed. Organistions are obliged to ensure safety for their staff. Trauma-informed care and supervision may be used. It has been shown that practitioners mostly experienced tense situations with elements of psycological abuse. Some practitioners did not report to be influenced by violent behavior, while others experienced negative consequences on their well-being, work or personal life. Practitioners developed their own approaches to ensure their safety. Some also used elements of models for working with involuntary users. Organisations ensured safety with supportive, physical ways and by forming violence prevention plans. It has been suggested that practiticioners should be educated about how to work with users' violence and involuntary users. Organisations should reflect on their work culture. Not only support and safety of the employees, but also respectful attitude towards users should be ensured.
Keywords: nasilje v družini; violence; neprostovoljni uporabniki; involuntary users; perpetrators; povzročitelji nasilja; safety; socialne službe; trauma; zaposleni; varnost; security; prevention; research; travme; preventiva; raziskave